Transmission losses allocation in deregulation electricity market - Ramani, Anis Niza; Baharin, Kyairul Azmi (2010)
The restructuring of Electricity Supply Industry (ESI) all over the world that started mainly in the 20th century introduces an open electricity market for trading electricity between generators and suppliers in competitive environments. This transformation consists of two aspects that are related with each other; restructuring and privatization. However, due to this change, some problems and challenges have risen. One of it is the issue of power losses allocation. When electrical power is transmitted through a network, it will cause power losses. The generators must compensate this loss by generating more power. Under competitive electricity market environment, no generators would want to generate more to compensate this loss as it will increase their production cost. Logically both generators and consumers are supposed to pay for the losses because they both use the network and thus are responsible for the losses incurred. If there is no specified method to handle this problem, there is a probability that the Independent System Operator (ISO) which is a non-profit entity and does not have source of income will be responsible for this losses. However, if ISO paid for the losses, it is considered unfair. It is the market participants who should cover up the cost of losses. Thus, this analysis focuses on some existing allocating transmission losses and loss cost methods. The selected methods are pro rata, proportional sharing and novel pricing and these methods have been tested using simple bus network and the IEEE standard 14 test bus system.